Literacy for conscientization: a framework for voter education in enhancing sustainable democratic governance in Nigeria (2017)
The Nigerian political system lacks a virile democratic culture as characterized by general political apathy and voter apathy especially among the illiterate adult population. There is lack of effective participation in the political process by the Nigerian citizens as a reflection of the poverty of political literacy. The grassroots people in Nigeria are yet to be adequately conscientized to be conscious of their rights in terms of critical awareness of the social, economic and political conditions which impoverish them. Conscientization leads to people organizing themselves to participate in democratic governance so as to change their social, economic and political realities. Thus, the significant impact of political literacy facilitated by voter education to empower the citizens for effective participation in the political process cannot be overemphasized. This paper examines literacy for conscientization as a framework for voter education in enhancing sustainable democratic governance in Nigeria.